Análise da resposta da fotobiomodulação no gânglio da raiz dorsal para tratamento da dor lombar crônica: estudo clínico e experimental na determinação do mecanismo de ação envolvido - Holanda, Vanessa Milanesi (2016)
Chronic axial low back pain is a complicated drawback in public health and has a high so- cioeconomic impact. OBJECTIVE: The aim of this study were to determine the response of laser irradiation in the dorsal root ganglion of the second lumbar spinal nerve for chronic axial low back pain compared to lidocaine injection and radiofrequency treatment and its mechanistic basis of photobiomodulation therapy for low back pain. MATERIAL and METHODS: This study was divided in PART I: Experimental studies which took place at the Department of Anatomy, Physi- ology and Genetics at the Uniformed Services University of the Health Sciences (USUHS), Bethes- da, Maryland, USA.; and PART II: Clinical study developed at Beneficência Portuguesa Hospital of São Paulo, Brazil. PART I: In vitro study: Rat DRG neurons were seeded and cultured on coat- ed slides for 48 hours. The cultures were randomly assigned to either control or to laser treatment (LT) groups for 2, 5, 30, 60 or 120s. The laser parameters were: output power= 960mW, power density= 300mW/cm2, 808nm wavelength, spot size= 3cm diameter and area= 7,07cm2. Forty minutes post laser, the MTS assay was applied to measure mitochondrial metabolic activity. Cells were also fixed with paraformaldehyde for immunocytochemistry with an antibody to β-Tubulin III visualized and photographed using fluorescence microscopy. In vivo study: 12 rats were divid- ed into three groups (n=4): 1) Control: surgery without LT, 2) Short term: surgery for spared nerve injury of common peroneal and tibial nerves with LT on day 7 and euthanized on day 7 af- ter behavior test, 3) Long term: surgery with LT on day 7 and euthanized on day 22. PART II: Clinical prospective, control, randomized study, in which thirty-one patients were divided into three treatment groups: G1) lidocaine injection, G2) radiofrequency, or G3) lasertherapy irradia- tion. The second intervertebral foramen between the second and third lumbar vertebrae was ac- cessed by percutaneous needle puncture bilaterally, guided by fluoroscopy. In the local anesthetic group, 1ml lidocaine injection without epinephrine was used through a 20-gauge (G20) quincke tip spinal needle inserted in the second lumbar intervertebral foramen. In the radiofrequency group, the probe (150mm long with a 5mm active tip) was directed through a G20 needle placed in the second lumbar intervertebral foramen and a pulsed radiofrequency neuromodulation was done, using Cosman G4® in pulses of 20ms with wash-out period of 480 ms, for 300 seconds at 42oC. In all groups a single treatment was applied. In the laser treatment group, a continuous wave (CW), 808nm wavelength diode laser (Photon Lase III® DCM, Brazil), with an output power of 100mW was used for a single treatment. An 18 gauge needle was placed in the second lumbar intervertebral foramen guided by fluoroscopy. Light irradiation was delivered through a 600μm optical fiber placed in the G18 needle. The tip of the fiber extended 5mm beyond the tip of the needle in the second lumbar intervertebral foramen. The beam spot size was 0.003cm2, irradiance = 35W/cm2, exposure time = 84 seconds, energy density = 2,800J/cm2, total energy was 8,4 J. The low back pain score was assessed by the visual analog scale (VAS) and Pain Relief Scale (PRS) pre, post procedure, in 1 and 12 months follow up. Temperature was measured using a digital ther- mometer. RESULTS: PART I: All the LT groups had statistically significant lower mitochondrial metabolism compared to controls. Within neuritis of DRG neurons with a diameter 30μm or less, varicosities and undulations were present. These neurons are associated with C and Aδ fiber types. The neuritis of DRG neurons with a diameter of greater than 30μm initiated to form vari- cosities only in the 120s group. For heat hyperalgesia, no significant difference was found between control and LT groups on 7 days post-injury. Within 1 hour post LT, the injured site presented significant less sensitivity to the heat stimulus compared to the ones before LT. For long term, LT causes less sensitivity to the heat stimulus than control group on Day 15 and Day 21. For cold al- lodynia, the injured site displayed significant less sensitivity to the cold stimulus within 1 hour after LT. For long term, the sensitivity to the cold stimulus returned to the control level after 5 days post-LT (Day 12). For mechanical hyperalgesia, the injured site indicated significant less sen- sitivity to the pin prick stimulus within 1 hour after irradiation with LT. For long term, the sensi- tivity to the pin prick stimulus also returned to the control level after 5 days post-LT on Day 12. For mechanical allodynia using electronic Von Frey test, no significant difference was seen for both immediate effect and long-term effect of LT between control and LT group. PART II: All patients in the local anesthetic and laser treatment groups reported a pain reduction of at least 50% immediately post-procedure and 10 out of 11 patients in the radiofrequency group reported a pain reduction of at least 50%. At 1 month post-treatment, the laser treatment group had the greatest number of patients who reported more than 50% pain relief, based on PRS (7 out of 10 patients), while only 5 out of 10 patients and 3 out of 11 patients in the lidocaine and radiofre- quency treatment groups, respectively, reported more than a 50% pain relief. In the radiofre- quency treatment group, for long term follow up (1 year), all the patients evaluated (9 out of 9) increased their pain to the same level to the previous procedure and also could not return to their daily life activities. In the lidocaine group, 1 out of 8 patients reported 50% pain relief based on PRS and this patient returned to his daily life activities. In the laser group, 4 out of 7 patients de- scribed more than 50% on PRS, but just one of them returned to her daily life activities, the other complained about disabled hip joint pain. Both patients considered themselves satisfied with the procedure, then pointing general improvement of their quality of life. CONCLUSION: Photobio- modulation therapy of the second lumbar dorsal root ganglion revealed a successful and long- lasting pain control when compared to lidocaine and pulsed radiofrequency. The decrease in mi- tochondrial metabolism and associated morphological changes in the neuritis may be directly re- lated to the mechanistic basis of photoneuromodulation of chronic low back pain observed clini- cally. This long-lasting conduction blockage presented in the clinical study is related to the mor- phological changes based on the components of the cytoskeleton of the different types of neurons, due to the use of a high-level irradiance in the interval of 270-300mW/cm2. Laser irradiation was more effective than the other two treatments employed, for long term chronic low back pain con- trol, without side-effects, and with cost-effectiveness.